Implementation of Positive School Culture in Developing Student Character: A Literature Review Study in Indonesian Elementary Schools - Sumarno, Edi; Nurul Istiq’faroh; Mochamad Nursalim (Jurnal Pendidikan Edutama, 2025)
This study investigates the implementation of positive school culture and its impact on character development in Indonesian elementary schools through a systematic literature review of studies from 2019-2024. Using qualitative analysis, the research identifies key components of successful character education programs and their integration into school environments. The findings reveal that effective character education is achieved through systematic implementation of five core values (Religious, Independent, Mutual Cooperation, Integrity, and Nationalism), supporting infrastructure, classroom reinforcement programs, and literacy culture development. Research shows that structured approaches to character education, combined with daily activities and teacher modeling, significantly impact student character formation. Additionally, proper facilities and positive cultural elements such as effective communication, teamwork, and inclusivity create conducive learning environments. The study concludes that positive school culture substantially influences student character development and academic achievement, providing practical insights for educational stakeholders.